Novel Form of Curcumin Improves Endothelial Function in Young, Healthy Individuals: A Double-Blind Placebo Controlled Study. (17th August 2016) - Oliver, Jonathan M.; Stoner, Lee; Rowlands, David S.; Caldwell, Aaron R.; Sanders, Elizabeth; Kreutzer, Andreas; Mitchell, Joel B.; Purpura, Martin; Jäger, Ralf
Abstract : Curcumin, a turmeric extract, may protect against cardiovascular diseases by enhancing endothelial function. In this randomized controlled double-blind parallel prospective study, fifty-nine healthy adults were assigned to placebo, 50 mg (50 mg), or 200 mg (200 mg) curcumin, for 8 weeks. The higher curcumin (200 mg) supplementation produced a dose-mediated improvement in endothelial function measured by flow-mediated dilation (FMD). The outcome was a clinically substantial 3.0% increase (90% CI 0.7 to 5.3%, p = 0.032 ; benefit : harm odds ratio 546 : 1) with the 200 mg dose, relative to placebo. The 50 mg dose also increased FMD relative to placebo by 1.7% (−0.6 to 4.0%, p = 0.23 ; 25 : 1), but the outcome was not clinically decisive. In apparently healthy adults, 8 weeks of 200 mg oral curcumin supplementation resulted in a clinically meaningful improvement in endothelial function as measured by FMD. Oral curcumin supplementation may present a simple lifestyle strategy for decreasing the risk of cardiovascular diseases. This trial was registered at ISRCTN registry (ISRCTN90184217 ).